Pd-functionalized carbon nanotubes for selective hydrogenation of 2-butyne-1,4-diol - Nadgeri, Jayprakash M.; Garade, Ajit C.; Tambe, Romana A.; Gokhale, Suresh P.; Rode, Chandrashekhar V. (Advanced Science Letters, 2010)
Multiwalled carbon nanotubes were prepared by thermal decomposition method followed by acid treatment and Pd-functionalization with PdCl2 by wet impregnation method. The Pd functionlized carbon nanotubes catalyst was characterized by BET, FT-IR, Raman, XRD, EDX, ICP-OES, SEM and TEM and was evaluated for its activity for hydrogenation of 2-butyne-1,4-diol. It showed higher selectivity (93%) to 2-butene-1,4-diol than Pd supported on commercial carbon (70% selectivity to 2-butene-1,4-diol) for complete conversion of 2-butyne-1,4-diol. The catalyst also exhibited excellent stability as evidenced by the three catalyst recycle experiments.